Skin whitening as a menace to African identity through Tony Morrison's 'The Bluest Eyes': An Afrocentric examination (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2021)
The African democratic forces, among other things, aimed to resuscitate and re-essentialise African identities that the colonial administration had endangered earlier. These autonomous corps dispensed mechanisms to champion Africanism and conscientise African natives about their heritage. The cherishing of African identities automated decolonial shifts and inculcated an urge into Africans to be proud of who they are and where they come from. Notwithstanding these efforts, the study diagnoses skin whitening as a stubborn nemesis that menaces the authenticity of Africanism in the present day. Many Africans, especially black women appear to be gravitated to skin whitening. This act embraces the attempt to alter one’s dark skin tone to be bright. Most of the skin whiteners are postulated to whiten their skins in an effort to qualify into the modern-day Eurocentric criterions of beauty at the expense of their black (African) identity. This paper employed a qualitative methodology and has relied on secondary data to unveil the extent to which skin whitening imperils African identities. It has employed Morrison’s The Bluest Eyes as a lens to crystalise the impacts of skin whitening on Africanism. The study has discovered that the skin-whitening phenomenon epitomises and perpetuates Eurocentric ideologies and it is preferred by most women because of the assumed glory that comes with the white identity such as social class, privilege, attractiveness, favour, and admiration.